Decreased T Cell Levels in Critically Ill Coronavirus Patients: Single-Center, Prospective and Observational Study - Xu J; Liu Z; Liu H; Luo Y; Kang K; Li X; Yang W; Fei D; Wang C; Yu K (Dove Medical Press, 2021)
Jingjing Xu,1 Zhiyu Liu,2 Haitao Liu,1 Yunpeng Luo,3 Kai Kang,3 Xueting Li,1 Wei Yang,3 Dongsheng Fei,3 Changsong Wang,1,3 Kaijiang Yu3 1Department of Critical Care Medicine, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang Province, People’s Republic of China; 2Department of Laboratory Diagnostics, First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 3Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of ChinaCorrespondence: Changsong WangDepartment of Critical Care Medicine, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang Province, People’s Republic of ChinaEmail changsongwangicu@163.comKaijiang YuDepartment of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, No. 23 Youzheng Street, Harbin, Heilongjiang Province, People’s Republic of ChinaEmail drkaijiang@163.comBackground: Since Dec. 2019, the COVID-19 pandemic has been an outbreak. T cells play an important role in dealing with various disease-causing pathogens. However, the role of T cells played in COVID-19 patients is still unknown. Our study aimed to describe the immunologic state of the critically ill COVID-19 patients.Methods: A total of 63 patients with confirmed COVID-19 pneumonia were admitted to the Department of Intensive Care Unit of the First Affiliated Hospital of Harbin Medical University. The immunologic characteristics (lymphocyte apoptosis, the expression of PD-1 and HLA-DR in T cells, T cell subset levels, redistribution and the production of inflammatory factors) as well as their laboratory parameters were compared between severe group and critical group.Results: The level of T cells in peripheral blood was decreased in critical patients compared with that in severe patients, but the expression levels of PD-1 (CD4+: 24.71% VS 30.56%; CD8+: 33.05% VS 32.38%) and HLA-DR (T cells: 36.28% VS 27.44%; monocytes: 20.58% VS 23.83%) in T cells were not significantly changed, and apoptosis and necrosis were not different in lymphocytes (apoptosis: 1.04% VS 1.27%; necrosis: 0.67% VS 1.11%), granulocytes, or monocytes between those two groups.Conclusion: There is severe immunosuppression in critically ill COVID-19 patients. Redistribution of T cells might be the main reason for lymphocytic decline. Decreasing the infiltration of T lymphocytes in the lung may be beneficial for the treatment of COVID-19.Keywords: COVID-19, T lymphocytes, PD-1, HLA-DR, redistribution